Contemporary theories of beauty and decorum. An overview of 20th century ideas - Karol Klauza (Sacrum et Decorum, 2022)
The aim of this study is an attempt to continue the discussion started by the extremely useful and competent synthesis of views on the relations between art and matter, presented in the article The Transformations of the Symbolic and Theological Meaning of Matter Reflected in Christian Aesthetics and Art by Janusz Królikowski Since the 16th century, European thought on the nature of beauty has been marked by interpretations that draw on the achievements of many academic disciplines. Numerous secular views on aesthetics were expressed in the period between the Baroque and positivism, and the ecclesiastical ones between the era of post-Tridentine theology to the time of accomodata renovatio of the Second Vatican Council and the concept of culture born out of it. Philosophers and art historians, especially of the nineteenth century, sought new justifications for changing views on beauty and its role in building the generational identity of the human being. In the field of philosophy, the views of George Berkeley and Immanuel Kant, among others, are experiencing a renaissance, and in religious thought, the same is true for the views of Joseph Ratzinger, prefect of the Congregation for the Doctrine of the Faith during the pontificate of John Paul II, concretised by the thought of Hans Urs von Balthasar. They correspond with the ideological inspirations of contemporary artists. Christian Churches undertake a dialogue with them in their Magisterium. In this way they develop elements of Christian aesthetics. Polish researchers have also made their contributions to this field.